Branded Drug Planning Based on (Combination) of Consumption Methods With ABC Analysis and Reorder Point (ROP) its Effect on Inventory Value and Turn Over Ratio (TOR) in the Pharmacy Installation of X Hospital, Bekasi - Muhammad Sapuan; Shirly Kumala; Sri Widyastuti (Jurnal Info Sains : Informatika dan Sains, 2025)
Planning drug needs in the Pharmacy Installation at Hospital X Bekasi, using the consumption method. This causes shortages and excess stock of branded drugs so that the drugs are not used and expire. The high value of branded medicine inventory at Hospital The aim of this research is to determine the difference in inventory value and Turn Over Ratio (TOR) of fast moving branded drugs after testing the application of a branded drug planning model based on a combination of consumption methods with ABC analysis and reorder points compared to the planning before testing in Hospital Pharmacy Installations. X Bekasi. The type of research carried out was pre-experimental using analytical descriptive methods. The approach used in this research is cross sectional. In-depth interviews and Focus Group Discussions were also conducted. The trial was carried out on fast moving ABC branded drugs for 3 months, namely June-August 2023. The quantitative approach was by calculating the inventory value and TOR value of fast moving group A, B and C branded drugs, before and after the trial. The research results prove that the application of model trials can reduce the inventory value of ABC fast moving branded drugs from IDR 124,848,282 to IDR 122,454,522, increase the TOR of ABC fast moving branded drugs from 5.66 to 8.12 and obtain an efficiency of IDR 2,393,760. The conclusion of this research is that planning for fast moving ABC branded drugs based on a combination of consumption methods with ABC and ROP analysis has been proven to reduce inventory value and increase TOR and obtain an efficiency of 1.92%.